2020
DOI: 10.1136/oemed-2019-106269
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime cumulative exposure to rubber dust, fumes and N-nitrosamines and non-cancer mortality: a 49-year follow-up of UK rubber factory workers

Abstract: ObjectivesTo examine associations between occupational exposures to rubber dust, rubber fumes and N-nitrosamines and non-cancer mortality.MethodsA cohort of 36 441 males aged 35+ years employed in British rubber factories was followed-up to 2015 (94% deceased). Competing risk survival analysis was used to assess risks of dying from non-cancer diseases (respiratory, urinary, cerebrovascular, circulatory and digestive diseases). Occupational exposures to rubber dust, rubber fumes, N-nitrosamines were derived bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… 51 However, while a small increased mortality risk was observed for ischemic and hemorrhagic stroke, no associations were detected for IHD. Further, cumulative exposure to rubber dusts, fumes and N‐nitrosamines have shown to increase the risk of IHD mortality in male rubber factory workers 52 . Seemingly, the overall lack of supporting evidence to explain some of the high, increased associations we detected for female workers across such industries, highlights an important gap in the literature.…”
Section: Discussionmentioning
confidence: 74%
“… 51 However, while a small increased mortality risk was observed for ischemic and hemorrhagic stroke, no associations were detected for IHD. Further, cumulative exposure to rubber dusts, fumes and N‐nitrosamines have shown to increase the risk of IHD mortality in male rubber factory workers 52 . Seemingly, the overall lack of supporting evidence to explain some of the high, increased associations we detected for female workers across such industries, highlights an important gap in the literature.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, tobacco smoke, a well-established risk factor for bladder cancer, is a main source of exogenous exposure to nitrosamines. A recent large cohort of British rubber workers with 49 years follow-up revealed that N-nitrosamines exposure was also associated with mortality from bladder cancer (19). Finally, heterocyclic amines and polycyclic aromatic hydrocarbons, which are formed by high temperature cooking, may also mediate the association between consumption of processed red meat and bladder cancer risk (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis viral infection, alcohol, aflatoxins, environmental and industrial pollutants, and air and water contamination are the most common factors linked with liver cancer [4]. Diethylnitrosamine (DEN) is a wellknown hepatocarcinogenic agent found in cigarette smoke, water, cured and fried foods, cheese from cheddars, chemicals from the farming industry, cosmetics, and pharmaceutical products [5,6]. By inhibiting several enzymes involved in the DNA repair process, DEN causes liver cancer in the experimental animal model [7,8] in addition to activation of cytochrome P450 enzymes, forming reactive electrophile enzymes that cause oxidation stress, which contributes to cytotoxicity, mutagens and cancers [9].…”
Section: Introductionmentioning
confidence: 99%